Acculturation and adaptation of Syrian refugees in Turkey: the role of (dis)concordance of acculturation orientations and identity threat - Terzi, Imge (2020)
The present study examined the social psychological factors affecting the adaptation of Syrian refugees in Turkey. Specifically, building on the mutuality approach of acculturation, the current study considered both the role of refugees’ own acculturation orientations towards culture maintenance and contact with the Turkish society, refugees’ meta perceived acculturation orientations from the Turkish host society, and the impact of perceived (dis)concordance acculturation orientations on their psychological and sociocultural adaptation. Based on the concordance model of acculturation (Piontkowski, Florack, Hoelker, & Obdrzálek, 2000), it was expected that discordance on cultural maintenance and desired contact would relate to lower life satisfaction, and sociocultural adaptation, while predicting higher identity threat (perceived discrimination). One hundred and nine participants completed a questionnaire measuring the variables of interest (own and meta perceived of acculturation, perceived identity threat, sociocultural adaptation, and life satisfaction). Data were collected by the paper/pencil questionnaires. The results showed a negative association between culture maintenance and life satisfaction, contradicting previous findings. Extending previous research, refugees’ perceived acculturation orientations from Turkish citizens, particularly perceived desire for contact, was an important positive predictor of both sociocultural and psychological adaptation. Finally, perceived discordance of acculturation was negatively related to psychological and sociocultural adaptation, and positively related to perceived discrimination. Theoretical and practical implications of these results are discussed.